Design principles for interventions to develop higher education honors students’ well-being - Jolise 't Mannetje; Marjolein Heijne-Penninga; Debbie Jaarsma; Irene Visscher-Voerman (Journal of the European Honors Council)
Students who experience high wellbeing are better able to develop and perform. Personal resources can contribute to experiencing wellbeing and interventions can be used to develop them. However, it is not yet sufficiently clear what such interventions should look like to be effective. Therefore, this study focuses on formulating design principles for interventions aimed at developing four personal resources of honors students: self-efficacy, optimism, inquiry mindedness, and self-regulation. Data were collected in focus groups. Data showed that design principles for interventions to develop those four personal resources differ somewhat, but in common they combine group and individual activities, students are taught basic skills to help them directing their own development, they have an ongoing character and consist of recurring activities. The design principles can be used to design interventions to enhance honors students’ personal resources. Further research is needed into the design and effects of these interventions and possible generalisation.